Selection of paddle length in flat-water kayak: Art or science? - Diafas, V.; Kaloupsis, S.; Dimakopoulou, E.; Zelioti, D.; Diamanti, V.; Alexiou, S. (Biology of Exercise, 2012)
The aim of this study was to examine the feasibility of personalising the paddle length for flat - water kayakers based on their anthropometric characteristics. The sample consisted of 55 male (age 20.05 ± 4.67 yrs, height 176.2 ± 4.46 cm and weight 75.8 ± 7.89 Kg) and 26 female highly trained kayak athletes (age 19.07 ± 3.64 yrs, height 165.5 ± 5.73 cm, weight 60.4 ± 7.65 kg). Anthropometric measurements were taken from all participants. Paddle length (horizontal distance between blade tips), blade length (horizontal distance between the blade tip and that point on the shaft where the structure begins to flare outwards to form the blade), blade width (maximum width of the blade) and paddle weight of each athlete were measured. In order to accomplish the aim of the study a factor analysis (varimax) and multiple regression analysis was conducted. The results suggest that for the selection of correct paddle length for male kayakers the body morphology and body lengths are the factors they should take on account.